2019
DOI: 10.1021/acs.jpcc.9b01722
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption of Gadolinium (Gd3+) Ions on the Dibenzo Crown Ether (DBCE) and Dicyclo Hexano Crown Ether (DCHCE) Grafted on the Polystyrene Surface: Insights from All Atom Molecular Dynamics Simulations and Experiments

Abstract: All atom molecular dynamics simulations and experiments were performed to understand the adsorption behavior of gadolinium (Gd 3+ ) ion on the crown ethers grafted polystyrene (PS) surface. Two different types of crown ethers, viz., dibenzo crown ether (DBCE) and dicyclo hexano crown ether (DCHCE), were grafted separately on the PS surface to understand the adsorption behavior. We investigate the roles of Gd 3+ ion concentration and grafting density (ρ s ) of the crown ether on the adsorption behavior of Gd 3+… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 44 publications
5
15
0
Order By: Relevance
“…25 The details of the generation of an amorphous polymer surface are provided in previous work. 24 However, brief information is provided in Figure S1 in the Supporting Information. The molecular geometry and partial atomic charge calculation of the DBCE and DCHCE are performed by ChelpG scheme using density function theory calculations using Gaussian09 with B3LYP/6-31 G(d,p).…”
Section: Methodology and Simulation Detailsmentioning
confidence: 99%
See 3 more Smart Citations
“…25 The details of the generation of an amorphous polymer surface are provided in previous work. 24 However, brief information is provided in Figure S1 in the Supporting Information. The molecular geometry and partial atomic charge calculation of the DBCE and DCHCE are performed by ChelpG scheme using density function theory calculations using Gaussian09 with B3LYP/6-31 G(d,p).…”
Section: Methodology and Simulation Detailsmentioning
confidence: 99%
“…The Einstein relation is used for calculating the self-diffusion coefficient of UO 2 2+ . 24 3. RESULTS AND DISCUSSION 3.1.…”
Section: Methodology and Simulation Detailsmentioning
confidence: 99%
See 2 more Smart Citations
“…Considering the factors such as adsorption capacity and selectivity are the most direct indexes to assess the practicability of adsorbent, the comparison with other adsorbents used to adsorb REM ions was carried out. [35][36][37][38] As summarized in Table 4, it can be observed that the adsorption capacity of PEI-CMC-IIS is not the highest, but PEI-CMC-IIS simultaneously possesses comparable adsorption capacity and excellent selectivity under neutral conditions, which is superior to other adsorbents in some way. Moreover, the main advantages of PEI-CMC-IIS are the cost-effective design, good stability, easy separation, pollution-free for the treated water, satisfactory adsorption capacity and selectivity.…”
Section: Comparison With Other Adsorbentsmentioning
confidence: 99%